All-Russian Research Institute of Vegetable Breeding and Seed Production - integration of science and practice - V.F. Pivovarov (Овощи России, 2012)
The article summarizes the work undertaken in the Institute for last five years. VNIISSOK is a leader in the field of breeding and seed production of vegetable crops. Staff of the Institute solve a query of producers for food supply security in Russia.